2017
DOI: 10.1080/14786419.2017.1294172
|View full text |Cite
|
Sign up to set email alerts
|

Chemical profiling and biological properties of Neolitsea kedahense Gamble essential oils

Abstract: Hydrodistillation of the fresh stem and leaf of Neolitsea kedahense Gamble, collected from Gunung Jerai, Malaysia followed by the GC-FID and GC-MS analysis revealed the detection of a total of 47 constituents of which 28 (86.4%) from the stem and 31 (96.4%) constituents from the leaf. δ-Cadinene (17.4%), 1-epi-cubenol (11.8%), cyperotundone (9.0%), cis-cadin-4-en-7-ol (7.7%), τ-cadinol (7.1%) and α-cadinol (7.1%) were the principle constituents in the stem oil, whereas β-caryophyllene (18.9%), bicyclogermacren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The peak areas and retention times were measured by electronic integration. The injections were performed in three replications (Jani et al 2017).…”
Section: Extraction and Identification Of The Chemical Compositions O...mentioning
confidence: 99%
See 1 more Smart Citation
“…The peak areas and retention times were measured by electronic integration. The injections were performed in three replications (Jani et al 2017).…”
Section: Extraction and Identification Of The Chemical Compositions O...mentioning
confidence: 99%
“…The retention indices of the compounds were identified relative to the retention times of a series of n-alkanes (C6-C28). The relative proportions of the compounds were percentages obtained by peakarea normalization, with all relative response factors being taken as one (Jani et al 2017).…”
Section: Extraction and Identification Of The Chemical Compositions O...mentioning
confidence: 99%
“…var. pungens [ 89 ], Rhaponticum acaule (L.) DC [ 90 ], Acacia mollissima and Acacia cyclops [ 91 ] and Neolitsea kedahense Gamble [ 92 ] and Senna podocarpa (Guill. and Perr.)…”
Section: Effects and Possible Mechanisms Of Bcp On Diabetesmentioning
confidence: 99%
“…In E. arvense, Radulovic et al, 18 also reported trans-phytol as a major component but in a relatively lesser amount (10.06%). Cis-cadin-4-ene-7-ol (5.32%), which also contribute a major proportion of essential oil of E. diffusum, was previously suggested responsible for the antimicrobial activity 35,36 . This oxygenated bicyclic sesquiterpene has also been reported from some angiosperms, Neolitsea kedahense-7.7% 36 , Achillea coarctata 37 , but this is the first report from pteridophyte.…”
Section: Fig 1: Gc-ms Chromatogram Of Essential Oil Of E Diffusummentioning
confidence: 99%
“…Cis-cadin-4-ene-7-ol (5.32%), which also contribute a major proportion of essential oil of E. diffusum, was previously suggested responsible for the antimicrobial activity 35,36 . This oxygenated bicyclic sesquiterpene has also been reported from some angiosperms, Neolitsea kedahense-7.7% 36 , Achillea coarctata 37 , but this is the first report from pteridophyte. Kanchanapoom et al, studied the chemical composition of the aerial portion of E. diffusum growing in Thailand, by using 1 H-NMR and 13 C-NMR and four compounds, sammangaoside A, kaempferol 3-O-sophoroside, L-tryptophan and (3S, 5R, 6S, 7E, 9S)-megastigman-7-ene-5,6epoxy-3,9-diol 3-O-b -D-glucopyranoside were identified 38 .…”
Section: Fig 1: Gc-ms Chromatogram Of Essential Oil Of E Diffusummentioning
confidence: 99%